Preenrichment with Adipose Tissue-Derived Stem Cells Improves Fat Graft Retention in Patients with Contour Deformities of the Face - Muhammad M. Bashir; Muhammad Sohail; Fridoon J. Ahmad; Mahmood S. Choudhery (Stem Cells International)
Quick absorption of adipose tissue grafts makes the outcomes less satisfactory for clinical applications. In the current study, adipose tissue grafts were mixed with adipose tissue-derived stem cells (ASCs) to improve retention of adipose tissue grafts and to make the clinical outcomes of fat grafting more reliable. Adipose tissue was either injected alone (conventional group) or mixed with ASCs (stem cell group) before injection. In both groups, adipose tissue was injected at the site of contour throughout layers of tissues till visual clinical symmetry with the opposite side was achieved. The volume of injected fat graft was measured after 72 hours and 6 months using a B-mode ultrasound device connected with a 12 MH frequency probe. The percentage reduction in the volume of injected fat, physician satisfaction scores (Ph-SCs), and patient satisfaction scores (P-SCs) were also recorded. After 6 months, there was significantly lower fat absorption in the stem cell group as compared to the conventional group. Mean physician and patient satisfaction scores were significantly improved in the stem cell group. No significant adverse effects were noted in any patient. Significantly lower absorption of graft due to the use of ASCs improves the clinical outcomes of conventional fat grafting for contour deformities of the face. The current preenrichment strategy is noninvasive, safe and can be applied to other diseases that require major tissue augmentation such as breast surgery. This trial is registered with NCT02494752.